The fun widow's book tour : a novel - Fishman, Zoe (William Morrow, an imprint of HarperCollins Publishers, 2023)
To promote her memoir, widow Mia, to find her spark, embarks on a book tour during which she visits her three best friends and discovers if she can rewrite who she is now by revisiting who she was then, maybe she can reignite the spark for all of them.